BIANCHI TYPE-V WET DARK FLUID COSMOLOGICAL MODEL IN SCALAR TENSOR THEORY OF GRAVITATION - TADE*, S. D.; TOTE, MEGHA K. (International Journal of Mathematical Archive, 2018)
In this paper, Bianchi type-V metric is considered in the presence of wet dark fluid in scalar-tensor theory of gravitation formulated by Saez and Ballester (Phys. Lett. A 113:467, 1986). The exact solutions are obtained from the corresponding field equations in the form of spacial volume V. Some physical properties like expansion factor Î¸, shear scalar Ïƒ and the deceleration parameter q are also discussed.